Assessment of Mineral Nutrient Efficiency in Genetically Diverse Spinach Accessions by Biochemical and Functional Marker Strategies - Rashid, Madiha; Yousaf, Zubaida; Din, Ahmad; Munawar, Muneeb; Aftab, Arusa; Riaz, Nadia; Younas, Afifa; Alaraidh, Ibrahim A.; Okla, Mohammad K.; AbdElgawad, Hamada (Frontiers in Plant Science, 2022)
Leafy vegetable crops are considered as a natural source of mineral nutrients that could decrease the risk factor of many growth issues in children and adults. Spinach is globally considered as the most desirable leafy crop, due to its taste and nutrient richness along with greater nitrate contents and better nitrogen use efficiency. To evaluate the mineral nutrient efficiency of this crop, thirty genetically diverse spinach accessions were analyzed through nutritional and functional marker strategies. The accession 163,310 from Pakistan was found to be rich in minerals (sodium, calcium, potassium, zinc, and manganese) and nitrates. However, the oxalate contents were lesser in the accessions that had greater quantity of nutrients. These represented a negative correlation between mineral availability and oxalate accumulation in the leaves. To study the relationship of oxalates and minerals in the accessions, a functional marker analysis was performed, based on the genes involved in oxalate metabolism and disease resistance in spinach. High level of genetic polymorphism was observed among the accessions represented with 115 polymorphic bands out of 130 bands. Heat map clustering represented the accessions from Asian countries (Pakistan, India, China, and Iran) as the most adaptable accessions to the local environment. The correlation between nutritional and genetic analysis also revealed the nutrient richness of these accessions along with good oxalate metabolism and disease resistance. Hence, these accessions could be considered as useful genotypes in future breeding programs.